2012
DOI: 10.5755/j01.em.17.3.2108
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Public Debt and Other Determinants on the Economic Growth of Selected European Countries

Abstract: Public debt has diverse effects on GDP varying from country to country and resulting from a number of different factors. This project is dedicated to research the effects of various macroeconomic indicators on GDP, with an emphasis on debt related predictors, using a multiple linear regression model. Findings of this research confirm the hypothesis that country determinants influence the efficiency of public borrowing and its effect on GDP. Surprisingly, no relation between debt crisis, level of government deb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 16 publications
(11 reference statements)
0
5
0
3
Order By: Relevance
“…They found that the positive impact of accumulated public debt turned into negative effect between 80 percent and 94 percent in the European Union (the EU without the new member states). The hypothesis that the public debt may have a significant impact on GDP, in some cases, a negative impact depending on countryspecific differences, has been confirmed by Ribeiro, Vaicekauskas, and Lakstutiene (2012). In other cases, the GDP has been affected positively by public debt.…”
Section: Literature Reviewmentioning
confidence: 86%
“…They found that the positive impact of accumulated public debt turned into negative effect between 80 percent and 94 percent in the European Union (the EU without the new member states). The hypothesis that the public debt may have a significant impact on GDP, in some cases, a negative impact depending on countryspecific differences, has been confirmed by Ribeiro, Vaicekauskas, and Lakstutiene (2012). In other cases, the GDP has been affected positively by public debt.…”
Section: Literature Reviewmentioning
confidence: 86%
“…In fact, borrowing is positively and significantly correlated with an increase in economic growth. Similarly, other studies show fascinating empirical outcomes where economic openness and FDI are found to be co-integrated (Ribeiro, 2012).…”
Section: Introductionmentioning
confidence: 86%
“…Lamminmaki and Leitch (2011) noted that nearly 80 percent of transactions are based on sales of goods or services for credit. The analysis of the scientific literature has revealed that a number of scientists -Snieška, Drakšaitė (2013), Ribeiro et al (2012), Sokolov, Sokolova (2012) and others -have researched the issues of public debt and its impact on economics, whereas the issues of debts in private sector have not earned sufficient scientific attention. According to Charitonov (2004), both global and Lithuanian economics are facing the problems of business insolvency.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Snieška and Drakšaitė (2013) studied the sustainability of public debt in small open economies and the impact of the public debt on economic growth. The influence of public debts on ECONOMICS AND CULTURE 13(01), 2016DOI: 10.1515/jec-2016 Brought to you by | MIT Libraries Authenticated Download Date | 5/11/18 3:12 PM economic growth of the European States as well as public debt advantages and disadvantages were analysed by Ribeiro et al (2012). According to Sokolov and Sokolova (2012), who researched the development and determinants of public debt, the issues of public debt have earned rather sufficient scientific attention, although they remain topical in the area of state management.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation